2012
DOI: 10.1021/jm301565b
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized RAD51 Inhibitor That Disrupts Homologous Recombination without Requiring Michael Acceptor Reactivity

Abstract: Homologous recombination (HR) is an essential process in cells that provides repair of DNA double-strand breaks and lesions that block DNA replication. RAD51 is an evolutionarily conserved protein that is central to HR. Overexpression of RAD51 protein is common in cancer cells and represents a potential therapeutic target in oncology. We previously described a chemical inhibitor of RAD51, called RI-1 (referred to as compound 1 in this report). The chloromaleimide group of this compound is thought to act as a M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 36 publications
(76 reference statements)
2
72
0
1
Order By: Relevance
“…In our irradiation study, we observed that MUC1-expressing cells stained less positively for γH2AX twelve hours post-irradiation in comparison to either control or MUC1-knock down cells (Figure 2a). Furthermore, we evaluated the role of non-homologous end joining repair (NHEJ) and homologous repair (HR) in DNA damage repair of MUC1-expressing cells using NHEJ inhibitor Nu-7026 and HR inhibitor RI-1, respectively (30,31). Both the treatments abrogated MUC1-induced differences in γH2AX staining as the level of γH2AX staining increased by combination treatments with DNA damage repair inhibitors and radiation (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…In our irradiation study, we observed that MUC1-expressing cells stained less positively for γH2AX twelve hours post-irradiation in comparison to either control or MUC1-knock down cells (Figure 2a). Furthermore, we evaluated the role of non-homologous end joining repair (NHEJ) and homologous repair (HR) in DNA damage repair of MUC1-expressing cells using NHEJ inhibitor Nu-7026 and HR inhibitor RI-1, respectively (30,31). Both the treatments abrogated MUC1-induced differences in γH2AX staining as the level of γH2AX staining increased by combination treatments with DNA damage repair inhibitors and radiation (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…27,28 Similarly, we previously demonstrated that both RI-1 and RI-2 induce elevated levels of SSA activity. 19 By contrast, we found that 9h does not stimulate SSA, using a relevant concentration range that inhibits HR (Figure 5b). This suggests that 9h stabilizes nucleoprotein filaments in a nonfunctional state, which are incapable of D-loop activity and simultaneously shielded from related (e.g., RAD52-mediated) pathways that promote SSA.…”
Section: Optimization Of Ring Amentioning
confidence: 64%
“…Other characterized RAD51 inhibitors including our previously described inhibitors RI-1 and RI-2 act by preventing RAD51 from loading onto damaged DNA. 13,19 Compound 1 and its analogues represent potential cancer therapeutics aimed at sensitizing tumors to DNA-damaging therapies. Considering its high potency for inhibiting both D-loop formation and HR, compound 9h provides an important candidate for further investigation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RAD51 has been recognized as a potential oncotarget due to its critical role in HR, and contributes to an aggressive cellular phenotype and resistance to therapeutics. Several small molecule RAD51 inhibitors have been discovered by high-throughput screening of compound libraries, notably B02 [5][6][7] , the RI series [8][9][10] and the IBR2 series 11,12 ( Figure 1). Alternatively, a fragmentbased screening approach at Cambridge identified another series of compounds 13,14 ( Figure 1).…”
mentioning
confidence: 99%